Respuesta :

Answer:

Step-by-step explanation:

Recall any base that is raised to a negative power is simply the reciprocal of the base.

i.e [tex]x^{-1}[/tex] = [tex]\frac{1}{x}[/tex]

Using this knowledge, we can start simplifying the equation (see attached)

Ver imagen marcthemathtutor

Answer:

[tex]\frac{a^3b^2}{a^{-1}b^{-3}}=a^{4}b^{5}[/tex]  

Step-by-step explanation:

Given : Expression [tex]\frac{a^3b^2}{a^{-1}b^{-3}}[/tex]

To find : Multiply or divide as indicated. Leave your answer with no factors in the denominator.

Solution :

We know when two same term are in divide then their power get subtracted.

So, [tex]\frac{a^m}{a^n}=a^{m-n}[/tex]

Applying in the expression,

[tex]\frac{a^3b^2}{a^{-1}b^{-3}}=a^{3-(-1)}b^{2-(-3)}[/tex]

Solve the power,

[tex]\frac{a^3b^2}{a^{-1}b^{-3}}=a^{3+1}b^{2+3}[/tex]

[tex]\frac{a^3b^2}{a^{-1}b^{-3}}=a^{4}b^{5}[/tex]

Therefore, The solution is [tex]\frac{a^3b^2}{a^{-1}b^{-3}}=a^{4}b^{5}[/tex]